98 Comparing the effectiveness of anabolic implants in Santa Gertrudis sired steers versus Angus steers. (30th November 2020) - Reichhardt, Caleb C; Brady, Tevan J; Briggs, Reganne K; Smith, Laura A; Bowman, Brett; Garcia, Matthew D; Thomas, Aaron; Thornton, Kara J
Abstract: This research compared the use of implants in Bos indicus influenced animals versus Bos taurus in a feedlot setting. Twenty steers were blocked by weight and breed in a 2 x 2 factorial design examining two different breeds: Angus (AN; n = 10) or Santa Gertrudis influenced (SGI; n = 10), and two implant strategies: no implant (CON; n = 10) or a combined implant (CI; n = 10). Steers were randomly placed into pens equipped with GrowSafe® bunks, fed the same ration, and weighed and ultrasounded on days 0, 28, 56, 84, and 112. Blood was collected on days 0, 2, 10, 28, 56, 84, and 112. Backfat measurements (BF), weights, and blood urea nitrogen (BUN) were determined. Data were analyzed using repeated measures and the ProcMixed procedure of SAS, looking at the main effects of breed, implant, and breed*implant. There were no initial differences (P > 0.05) in weight between any of the main effects. The main effects of breed, implant, and breed*implant demonstrate that AN gained more (P < 0.05) weight than SGI, CI gained more (P < 0.05) weight than CON, and the AN that received a CI had increased weight gain when compared to the AN CON, SGI CON and SGI CI. There was no difference (P > 0.05) in weight gain between the SGI that received a CI vs CON, nor was there a difference (P > 0.05) between the CON SGI and AN. There was a treatment*breed interaction for BF (P < 0.05), with AN tending to put on more BF than SGI CON (P < 0.08). A breed*treatment interaction was also observed when analyzing BUN (P < 0.05). This research provides preliminary evidence suggesting that anabolic implants are not as effective in Bos indicus influenced animals when compared to Bos taurus animals.